(untitled) (Talenta Conference Series: Science and Technology (ST), 2019)
Pemanfaatan inhibitor alami untuk menghambat pembentukan kerak dari materi anorganik telah menjadi kebutuhan masa kini mengingat banyak inhibitor yang digunakan dalam industry tidak ramah lingkungan dan mahal. Pada penelitian ini, inhibitor alami dipelajari dari produk alami yang diberi nama inhibitor LS. Pengujian inhibitor LS dilakukan dengan metode eksperimen seeded pada suhu 90oC dan konsentrasi larutan CaCO3 0.050 M. Hasil menunjukkan bahwa seiring peningkatan konsentrasi inhibitor, semakin efektif juga kemampuan penghambatan terhadap pembentukan kristal CaCO3 yang diiringi dengan penurunan pH larutan. Dapat disimpulkan bahwa penambahan inhibitor LS dengan rentang konsentrasi 50-350 ppm dalam larutan CaCO3 0.050 M, mampu menghambat pembentukan kerat CaCO3 dengan persentase 27,78%. The use of green inhibitors to inhibit scale formation of inorganic materials have become a necessity these days considering the many inhibitors are used in the industry are not environmentally friendly and expensive. In this research, it has been investigated the green inhibitors from natural products called LS Inhibitor. Testing of LS inhibitor was performed by seeded experiment method at temperature of 90 ° C and concentration of CaCO3 growth solution of 0.050 M. The results showed that The higher the inhibitor concentration added the greater the effectiveness of the inhibitor in inhibiting the formation of CaCO3 crystals accompanied by the decrease in pH of the solution. It is concluded that the addition of LS inhibitor in the concentration range of 50-350 ppm in CaCO3 crystal growth solution at the concentration of 0.050 M is able to inhibit the scale formation of CaCO3 around 27-278 %.